Practical Electronic Design for Experimenters - Frenzel, Louis E., Jr (McGraw-Hill's AccessEngineering., 2020)
"This book covers the basics of electronics but the focus is on the overall design of the product. The author argues that design is really a product-level consideration and not something that happens at the circuit level. Therefore, the book provides the reader with information about ready-made circuits, off-the-shelf components, and other readily available parts. Then the focus shifts to the fundamentals of design, resources, power supplies, digital designs, embedded controllers, wireless applications, prototyping, as well as testing, troubleshooting, and debugging. The applications of strong design training can be fun and far-reaching, from autonomous robots to smart clothing".